miR-1205/DNAJB1 reverses docetaxel chemoresistance in human triple negative breast carcinoma cells via regulation of mutp53/TAp63 signaling - Yin Yongxiang; Zhang Jinqiu; Ma Tao; Chen Daozhen; Lu Daru (Acta Biochimica et Biophysica Sinica, 2021)
Chemoresistance is the major cause of therapeutic failure in human triple negative breast carcinoma (TNBC). Docetaxel (DOC), a first-line therapeutic drug in TNBC treatment, is limited for long-term use due to the development of chemoresistance. Thus, overcoming chemoresistance of DOC remains an important challenge to improve patient’s outcome of TNBC. In this study, we aimed to investigate the molecular mechanism behind DOC chemoresistance and the possible therapeutic effects of miRNAs. Utilizing qRT-PCR analysis, we discovered that miR-1205 is gradually downregulated in human triple negative breast carcinoma MDA-MB-231 and docetaxel-resistant MDA-MB-231 (MDA-MB-231/DOC) cells compared with Hs 578Bst normal human breast fibroblasts. Cell viability, cell cycle and apoptosis assays in MDA-MB-231/DOC cells indicated that miR-1205 overexpression enhances docetaxel sensitivity by reducing cell viability as well as inducing G2/M cell cycle arrest and cell apoptosis. Western blot analysis, dual-luciferase reporter assay, co-immunoprecipitation assay and chromatin immunoprecipitation assay revealed that miR-1205 overexpression disrupts the stable complex formation of DNAJB1, mutp53 and TAp63 by directly reducing DNAJB1 expression, which abates the sequestrating effect of mutp53 on TAp63, thereby leading to the enhanced DOC sensitivity in MDA-MB-231/DOC cells. Our findings demonstrate the role of the miR-1205/DNAJB1 axis in the docetaxel resistance of TNBC, which may offer a promising therapeutic approach to resolve docetaxel resistance in TNBC.